(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2023)
The maintenance of viable and stable Xanthomonas cells is crucial for the xanthan reliable research and industrial production. The method, storage and recovery conditions should preserve both viability and phenotypical and genotypical features. Here, the effectiveness classical methods on the long-term preservation of different Xanthomonas arboricola pv pruni strains was to determine. Strains were preserved by monthly sub-culturing in solid medium and lyophilization. After 12 years the viability of the strains, was assessed, as well as their productive capacity and the viscosity of the xanthan gum produced by these strains kept by lyophilization and sub-culturing. Among the lyophilized strains, only those stored at -18°C were viable after 12 years. The productive capacity of the strains were poorly affected by lyophilization, the passage of the cultures into a solid nutrition medium being sufficient for them to return to their normal metabolism. The viscosity of the synthesized xanthan gum was method-dependent and higher for the lyophilized strains. The work and its findings are new and original because a work on this topic has never been published before. The results obtained allow the breaking of paradigms regarding the preservation of Xanthomonas.